2017
DOI: 10.1007/s13760-017-0744-4
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of a new marker of transmyocardial repolarization parameters in ischemic stroke patients; T peak–T end (T p-e), T p-e/QTc

Abstract: The cardiovascular manifestations of acute ischemic stroke have been well known. Several electrocardiography (ECG) abnormalities have been reported in patients following acute stroke, including QT interval prolongation, ST segment deviation and T-wave changes. This study aimed to investigate the changes in transmyocardial repolarization parameters, in ischemic stroke patients. The study is a prospective, blind, and controlled clinical study. The patients without cardiac disease who received ischemic stroke dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…We have already carried out a study in our own department. This, and other studies in the literature, have shown a prolonged range of transmyocardial repolarisation parameters that have been proven to be associated with ventricular arrhythmias and sudden cardiac death in stroke patients [13,20,21]. In addition, these parameters were evaluated not only for stroke, but also for stroke severity, type, localisation, and prognostic value.…”
Section: Discussionmentioning
confidence: 81%
“…We have already carried out a study in our own department. This, and other studies in the literature, have shown a prolonged range of transmyocardial repolarisation parameters that have been proven to be associated with ventricular arrhythmias and sudden cardiac death in stroke patients [13,20,21]. In addition, these parameters were evaluated not only for stroke, but also for stroke severity, type, localisation, and prognostic value.…”
Section: Discussionmentioning
confidence: 81%
“…In this study, we found that, QTc, QTd, QTcd parameters are positively correlated with stroke severity. Emektar et al found that Tpe and Tpe/QTc parameters were significantly higher in acute ischemic stroke patients than control groups 25 . In our study, we found that Tpe and Tpe/QT parameters are positively correlated with stroke severity.…”
Section: Discussionmentioning
confidence: 98%
“…Учитывая цереброваскулярную эффективность афобазола при сосудистой патологии мозга и сердца, а также взаимосвязь между цереброваскулярными расстройствами и нарушениями функции сердца [44][45][46][47][48] были изучены антиаритмические свойства препарата.…”
Section: антиаритмические свойства афобазолаunclassified